Oxidant-Antioxidant Balance during On-Pump Coronary Artery Bypass Grafting. (18th August 2014) - Mentese, Umit; Dogan, Orhan Veli; Turan, Ibrahim; Usta, Sefer; Dogan, Emre; Oztas Mentese, Seda; Demir, Selim; Ozer, Tanil; Aykan, Ahmet Cagri; Alver, Ahmet
Abstract : Backround . The aim of this study was to evaluate the changes in perioperative oxidant-antioxidant balance in ONCABG. Methods . Twenty-three patients were included in this study. Serum total oxidant status (TOS), total antioxidant status (TAS), and oxidative stress index (OSI) values were assessed preoperatively, at 20 minutes after aortic clamping and at 30 minutes, 6 hours, and 48 hours after declamping (reperfusion). The patients were divided into 2 groups according to the median aortic cross clamping (XC) time: group 1 (XC time < 42 minutes) and group 2 (XC time ≥ 42 minutes). Results . TOS and OSI values of whole patients at 30 minutes after reperfusion were higher than preoperative values (P = 0.045, P = 0.015 ), while perioperative TAS levels of the patients were similar to the preoperative levels (P = 0.173 ). XC time was correlated with TOS levels at 30 minutes after reperfusion (r = 0.43, P = 0.041 ). In group 2, TOS and OSI values at 30 minutes after reperfusion were higher than preoperative values (P = 0.023, P = 0.048 ), whereas a significant difference was not found in group 1 (P = 0.601, P = 0.327 ). Conclusions . Oxidative imbalance and increase in TOS at reperfusion in ONCABG may be associated with XC time.